Recovery of Hydrogen Sulfide, Copper and Cobalt from the Samples after Conversion of Pyrite to FeS - ZIYADANOGULLARI, RECEP; AYDIN, FIRAT (Asian Journal of Chemistry, 2010)
The aim of this study was to recover hydrogen sulfide, copper and cobalt from the pyrite samples provided from Ergani and Küre Copper Mining Co., Turkey. The samples were subjected to two different processes: in first process, the sample was mixed with different rates of iron at varying temperature and time and then subjected to roasting process in closed vessel system. In the second process, the sample was directly exposed to roasting process in a closed vessel system. In both processes, conversion values of pyrite into FeS were determined. After direct roasting the pyrite at 725ºC for 1 h, the conversion rate of pyrite into FeS was found to be 98.9 ± 0.1 %. By addition of H2SO4 the sample converted into FeS structure, H2S gas was formed. Through reaction of water with the residue remaining after separation of H2S gas from solid phase, iron passed into solution, while copper and cobalt remained in the solid phase. In order to recover cobalt and copper from the sample in which iron was removed, two procedures were followed; first procedure includes taking cobalt and copper in solution by direct roasting the sample in air atmosphere at 600ºC. The second process involves taking cobalt and copper in solution medium trough roasting the sample under the same conditions after enrichment with flotation. As a result of roasting the samples enriched with flotation, the optimal conditions in which copper and cobalt could be taken into solution with high yield were determined.